UTILIZATION OF LIME PEELS AND INCREASING THE VALUE OF LIME PRODUCTION IN BOLO VILLAGE, GRESIK USING NANOTECHNOLOGY - Tahta Amrillah; Intan Nurul Rizki; Mochamad Lutfi Firmansyah; Ilma Amalina; Prastika Krisma Jiwanti; Muchammad Farchan Chanif; Yeremia Budi Cristian; Muhammad Aditya Bryan Rahadi; Muhammad Fahrizal Himawan; Retno Sari (Jurnal Layanan Masyarakat, 2023)
The people of Bolo Village, Ujung Pangkah District, Gresik Regency, choose to farm as a livelihood, both as farmers on their own land and on other people's land. Lime is a type of plant that is widely grown in the area. With a lime garden area of 450 hectares, lime farmers in this area can produce an average of 2-3 tons of lime per month per hectare. Lime from this sub-district has also reached local and international markets, such as Malaysia and Singapore. The community also develops or processes lime into processed products that have higher economic value, for example processed into processed beverage products in the form of liquids, extracts, instant powders, or processed into belt products, cosmetics and so on. On the other hand, technological developments that are rapidly developing can basically be used to increase the marketability of limes, such as processing lime peels into more useful products, not just lime contents. Nanotechnology can be used to produce lime peel powder with a nanometer size using a tool called a ball mill and grinder. The process of making lime peel nanopowder using a ball mill is very simple. This tool has also been developed a lot so the price is also cheap. For this reason, the community service activities is carried out to provide education to lime farmers in the Ujung Pangkah sub-district, Gresik to process lime peels into powder and make it possible to obtain nanopowder which has high selling value and or produces processed lime into other products. The expected output is lime peel processed products into powders of various sizes, one of which is nanometer with a lime peel powder maker, in this case a ball mill and grinder with simple operations and low prices. In simple terms, especially large powders can be used as additional ingredients for spices, even tea mixtures. This community service activity can support the 12th point of the Sustainable Development Goals in promoting zero waste, namely responsible consumption and production; as well as on point 8, namely decent work and economic growth in encouraging the formation of MSMEs to utilize processed orange peels to increase their economic value. Thus, we also believe that the community service would not only increase the lime home industry in Bolo village significantly, but also increase awareness of the community about the environmental sustainability.